Exome sequencing identifies a novel EP300 frame shift mutation in a patient with features that overlap cornelia de lange syndrome. Issue 1 (29th October 2013) - Woods, Susan A.; Robinson, Haynes B.; Kohler, Lisa J.; Agamanolis, Dimitris; Sterbenz, George; Khalifa, Mohamed
<x xml:space="preserve">Abstract</x> Rubinstein–Taybi syndrome (RTS) and Cornelia de Lange syndrome (CdLS) are genetically heterogeneous multiple anomalies syndromes, each having a distinctive facial gestalt. Two genes (CREBBP and EP300) are known to cause RTS, and five (NIPBL, SMC1A, SMC3, RAD21, and HDAC8) have been associated with CdLS. A diagnosis of RTS or CdLS is molecularly confirmed in only 65% of clinically identified cases, suggesting that additional causative genes exist for both conditions. In addition, although EP300 and CREBBP encode homologous proteins and perform similar functions, only eight EP300 positive RTS patients have been reported, suggesting that patients with EP300 mutations might be escaping clinical recognition. We report on a child with multiple congenital abnormalities and intellectual disability whose facial features and complex phenotype resemble CdLS. However, no mutations in CdLS‐related genes were identified. Rather, a novel EP300 mutation was found on whole exome sequencing. Possible links between EP300 and genes causing CdLS are evident in the literature. Both EP300 and HDAC8 are involved in the regulation of TP53 transcriptional activity. In addition, p300 and other chromatin associated proteins, including NIPBL, SMCA1, and SMC3, have been found at enhancer regions in different cell types. It is therefore possible that EP300 and CdLS‐related genes are involved in additional shared pathways, producing overlapping phenotypes. As whole exome sequencing becomes more widely utilized, the diverse phenotypes associated with EP300 mutations should be better understood. In the meantime, testing for EP300 mutations in those with features of CdLS may be warranted. © 2013 Wiley Periodicals, Inc.